Changes in the skeletal dimensions of the digits of the thoracic limb of Holstein cows after maturation. (22nd January 2020) - Oishi, Motoharu; Kamijo, Keiji; Iitani, Kana; Sato, Reiichiro; Yamada, Kazutaka; Ichihara, Nobutsune
Abstract: The 12 left digits of the thoracic limb of Holstein female cows were obtained from a slaughterhouse, and 13 linear measurements of skeletal specimens of the digits of the thoracic limb were used in this study. Bivariate plots, regressions and correlation analyses were performed to assess the relationships between osteometric data and age, and between osteometric data and body size. The geometric mean (GM) of the metacarpal size was used as a proxy of body weight. The results of the regression analysis demonstrated that the length and the width of the distal phalanx were significantly correlated with age, whereas those of other bones were not. In addition, the correlations of the distal phalanx tended to be higher with age than with the GM of the metacarpal size, and their skeletal measurements tended to be longer in older animals than in younger animals. These findings suggest that the distal phalanx is slightly elongated and enlarged in its solear aspect with increasing age in skeletally mature cows. Moreover, although the side difference in the distal phalanx between the lateral and medial digits did not increase significantly with age, the solear aspect of the distal phalanx tended to be rougher, and deformation of the flexor tubercle tended to be more pronounced in the medial digit compared with the lateral digit. Therefore, in the distal phalanx of the front feet, the skeletal deformation with age and asymmetrical bone development might be related to the pathogenesis of claw horn lesions, as in the hind feet.